Stranded and equilibrated assemblages of late feldspars in two granitic pegmatites in the Pampean Ranges, Argentina - Cerny, Petr (2003)
Late primary K-feldspar in two granitic pegmatites from the Pampean pegmatite province in Argentina shows similar patterns of growth and exsolution, but different structural states and mineral associations. (i) In El Criollo, a beryl - columbite - phosphate pegmatite in the Punilla pegmatite field, a single miarolitic cavity in the blocky zone is lined with pale rusty crystals of veinperthitic K-feldspar and quartz. The Kfs host, Or89.7 Ab7.8 Rbf0.3 LEf(? 1.1 (□Si4O8)1.2 (∼88 vol.%), corresponds to optically and XRD-monoclinic, but highly (Al,Si -ordered orthoclase (2t1 = 0.82), with only a slight incipient conversion to intermediate grid-twinned microcline along contacts with exsolved low albite, Ab98.1 An1.2 Or0.9 (∼12 vol.%). The homogeneous precursor of the perthite contained ∼22 mole % Abss. The perthitic orthoclase is overgrown, mainly on the {010} faces, by nonperthitic, gemmy, pale grey to beige orthoclase, Or91.6 Ab6.1 Rbf0.5 Cno.2 Srf0.1 LEf(?)0.2 (□Si4O8)1.5, with 2t1 equal to 0.84. Small tabular crystals of white low albite, Ab99.5 Or0.7, elongate parallel to c, are situated on the {010} faces of the orthoclase in epitactic orientation. (ii) In San Luis II, a spodumene pegmatite in El Totoral pegmatite field, crystals of coarsely perthitic K-feldspar and quartz line cavities in the core-margin zone. The mottled-grey euhedral K-feldspar, Or92.3 Ab4.1 Rbf1.1 Csf0.1 Cn0.1 Srf0.1 LEf(?)1.5 (□Si4O8)0.8 (∼92 vol.%), locally altered to muscovite and clay minerals, is very close to end-member low microcline with vein-shaped exsolution lamellae of low albite. Ab99.1 An0.1 Or0.4 Cn0.1 Srf0.1 (∼8 vol.%). The homogeneous precursor of the perthite contained ∼13 mole % Abss. All faces of the perthite crystals have an even overgrowth of pale grey, nonperthitic low microcline, Or92.8 Ab4.8 Rbf0.2 Srf0.1 LEf(? 1.8(□Si4O8)0.3. The cavity space among the crystals of the K-feldspar and primary quartz is largely filled by microcrystalline secondary quartz, "chalcedony", opal and goethite. Different subsolidus histories of the two host vugs explain the conspicuous contrast between the structural states of their cavity-lining K-feldspar. In El Criollo pegmatite, the cavity probably quickly lost residual aqueous fluid, as the orthoclase of both the primary perthitic crystals and particularly of the gemmy overgrowth show only stranded, coherent domain-scale order and twinning, and very limited alteration. In the San Luis II pegmatite, the cavity-lining K-feldspar shows considerable alteration and overgrowth by low-temperature phases, indicative of substantial hydrothermal activity, which promoted (Al,Si)-ordering to give tartan-twinned low microcline in both the primary perthitic crystals and the norperthitic overgrowths.